Genome Sequencing of Blacklip and Greenlip Abalone for Development and Validation of a SNP Based Genotyping Tool - Kijas, James; Hamilton, Matthew; Botwright, Natasha; King, Harry; McPherson, Luke; Krsinich, Anton; McWilliam, Sean (Frontiers in Genetics, 2019)
Abalone breeding in southern Australia often involves the production of interspecies hybrids through crossing blacklip (Haliotos rubra) and greenlip (H. laevigata) parental populations. To assist applied breeding and investigate genetic divergence, this study applied genome sequencing and variant detection to develop and validate a SNP genotyping tool. Skim short read Illumina sequencing was performed using 24 individuals from each of the two parental species and a hybrid population. Raw reads were assembled into three population specific pools (each 12–15 fold coverage), before mapping was performed against a draft greenlip abalone reference genome. Variant detection identified 22.4 M raw variants across the three populations (SNP and indels), suggesting they are highly heterozygous. First stage filtering defined a high quality SNP collection of 2.2 M variants independently called in each of the three populations. Second stage filtering identified a much smaller set of variants for assay design and genotyping using a validation set of 191 abalone of known population and pedigree. Comparison of allele frequency data revealed a high proportion of SNP (43%) had divergent allele frequency (< 0.2) between the two parental populations, suggesting they should have utility for parentage assignment. A maximum likelihood approach was used to successfully assign 105 of 105 progeny to their known true parent amongst a set of 86 candidate parents, confirming the genotyping tool has utility for applied breeding. Analysis of pairwise allele sharing successfully discriminated animals into populations, and PCA of genetic distance grouped the hybrid animals with intermediate values between the two parental populations. The findings present a library of DNA polymorphism of utility to breeding and ecological application, and begins to characterize the divergence separating two economically important aquaculture species.